ANALYSIS OF THE INFLUENCE OF LEADERSHIP AND COMMUNICATION STYLES ON EMPLOYEE SATISFACTION AT CAFES IN TEBING TINGGI CITY - Carnelius Ricardo; Musparina; Mangasi Sinurat; Willy Cahyadi (CV. Radja Publika, 2025)
This study aims to analyze the influence of leadership and communication styles on employee satisfaction in cafes in Tebing Tinggi City. The rapidly growing cafe industry demands effective human resource management, particularly in creating a supportive work environment through good leadership and effective communication. This study uses a quantitative approach with a sample of 50 permanent employees from 10 cafes selected using a purposive sampling technique. The research instrument was a questionnaire with a 5-point Likert scale, and data were analyzed using the Partial Least Squares (PLS) technique through the SmartPLS 3.0 application. The results of the study indicate that leadership style has a significant effect on employee satisfaction with a t-statistic value of 4.770 (p = 0.001), and communication also has a significant effect with a t-statistic value of 4.848 (p = 0.000). The research model has an R² value of 0.796, which means that 79.6% of the variability in employee satisfaction can be explained by leadership style and communication. The Q² value of 0.7960 indicates that the model has strong predictive relevance. These findings indicate that leadership style and communication play an important role in increasing employee job satisfaction, which impacts their performance and loyalty to the organization. This study recommends that café managers continue to improve the quality of leadership and internal communication to create a more productive and harmonious work environment.